KAJIAN ADAPTASI WILAYAH TERHADAP KETERSEDIAAN SUMBER DAYA AIR DI KAWASAN KRISIS AIR, SUB DAS WAKUNG C. HULU, DAS COMAL, KABUPATEN PEMALANG - Nugrahini Sandy Aji; Wiwandari Handayani (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2017)
Regional planning is commonly conducted by considering administrative boundary, however, it should not do in environmentally regional planning. In this case, there is water crisis area in Wakung Comal Hulu Sub Watershed. Although 64% of them is covered by forest. It located in the growth centre of Pulosari Sub District. Thus that condition affecting the water need of the community in household and agriculture. This phenomenon becomes the background of the research regarding the regional adaptation the water resource availability. This research use mix method with exploratories sequential model. Furthermore, it uses many technique analysis such as descriptive qualitative and scoring. To collect the data, this research use non-probability sampling particularly purposive sampling.The result of study found the kind of adaptation levels. They are high, optimal and low. Furthermore, the optimal adaptation dominated about 63% of them. the optimal adaptation is an ideal type. Because it contains an equality in morphology, physiology, and behavioural adaptation and so does stakeholder’s role. The unique point is the government and private sector has no causative relationship. Thus, it necessary to enhance the role of private sector.